Rancang Bangun dan Uji Kinerja Mesin Perajang Kentang dengan Penggerak Motor Listrik Menggunakan Sistem Sentrifugal Berkapasitas 30 Kg/Jam - Sunarto, Sunarto; janitra, Atika ayu; Arifin, Danu Nur; Riyanto, Dwi Slamet (Journal of Mechanical Engineering and Applied Technology, 2023)
This chopper machine is a machine used for slicing potatoes in the manufacture of chips. This machine is made to simplify the process of slicing potatoes. This machine is also equipped with a potato press and a machine housing cover. The planning process of engine manufacture begins with consideration of design alternatives which contain several design options to be considered, so that at the evaluation stage one of the best designs can be selected which is then developed towards the manufacture of all machine parts. This potato chopper machine is made using motor power calculations, shaft calculations, belt calculations, bearing calculations, peg calculations, and stretch calculations. This machine has dimensions of 600 mm Ã— 400 mm Ã— 1000 mm with a 0.25 HP electric motor drive. Setting the knife before using the machine to get the desired thickness of the sliced results, the use of material should be chosen stainless steel (stainless steel) to provide hygiene for food.